2019
DOI: 10.1111/mpp.12892
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber mosaic virus 2b proteins inhibit virus‐induced aphid resistance in tobacco

Abstract: Cucumber mosaic virus (CMV), which is vectored by aphids, has a tripartite RNA genome encoding five proteins. In tobacco (Nicotiana tabacum), a subgroup IA CMV strain, Fny-CMV, increases plant susceptibility to aphid infestation but a viral mutant unable to express the 2b protein (Fny-CMV∆2b) induces aphid resistance. We hypothesized that in tobacco, one or more of the four other Fny-CMV gene products (the 1a or 2a replication proteins, the movement protein, or the coat protein) are potential aphid resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…Plant viral diseases are one of the most important pathogens causing agricultural losses. Currently, the emergence and reemergence of insect-transmitted plant viruses in the past decades have been mainly driven by planthoppers, whiteflies, aphids and thrips [116][117][118][119][120]. We and many other groups in the world have developed several biotechnological methods to improve crop resistance against these vector-borne viruses with the expression of virus-targeting RNA interference [121][122][123].…”
Section: Perspectivesmentioning
confidence: 99%
“…Plant viral diseases are one of the most important pathogens causing agricultural losses. Currently, the emergence and reemergence of insect-transmitted plant viruses in the past decades have been mainly driven by planthoppers, whiteflies, aphids and thrips [116][117][118][119][120]. We and many other groups in the world have developed several biotechnological methods to improve crop resistance against these vector-borne viruses with the expression of virus-targeting RNA interference [121][122][123].…”
Section: Perspectivesmentioning
confidence: 99%
“…Infectious RNA mixtures for these reassortant and recombinant viruses were used to inoculate Nicotiana benthamiana plants for preparation of virions to use as inocula for experiments with A. thaliana (Palukaitis, 2019). We recently used a similar approach with Fny-CMV/LS-CMV reassortants to successfully identify the viral RNA conditioning antibiosis (strong resistance) against aphids in Nicotiana tabacum (Tungadi et al, 2020). RNA was isolated from systemically infected leaves, subjected to reverse transcription-PCR (RT-PCR) to amplify RNA 2-specific sequences and these amplicons sequenced to confirm that all recombinant RNA 2 molecules were genetically stable and did not undergo further mutation during replication and movement through the plant.…”
mentioning
confidence: 99%
“…The recombinant RNA 2 used to constitute this reassortant virus possesses the ORF for the Fny-CMV 2b protein (Figure 1b). The Fny-CMV 2b protein can induce a variety of effects on performance of aphids on tobacco plants infected with Fny-CMV (Ziebell et al, 2011;Tungadi et al, 2020) and in 2b-transgenic A. thaliana plants (Westwood et al, 2013). However, because infection with F1-L 1-300 F-F3 did not induce F I G U R E 1 Design of recombinant CMV RNA 2 molecules to identify CMV 2a protein sequences that influence plant-aphid interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, tobacco plants infected with CMV∆2b showed a dramatic reduction in aphid populations, indicating that the 2b protein was able to repress resistance to aphid infestation in tobacco. By using viral reassortants created by shuffling the genomic RNAs from Fny-CMV and LS-CMV strains, Tungadi et al [34] showed that in tobacco, Fny-CMV but not LS-CMV RNA 1 (or its 1a protein, a replication-associated factor) triggers resistance to aphids, while the 2b protein of both strains suppressed aphid resistance. In contrast, in arabidopsis aphid antibiosis is induced by Fny-CMV 2b protein and 1a prevents 2b's effect [35].…”
Section: The Interplay Between CMV 2b and Ja Signallingmentioning
confidence: 99%